The Level Of Education And Knowledge Associated With Complience Of Health Care Workers For Triage Implementation - Eka Surasa; Siti Nurunniyah; Zulpahiyana Zulpahiyana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Triage is a process of patients classification based on the type and the level of emergency condition in health services especially in Emergency Room (ER). In the ER, Health Care Workers (HCWs) never know when do patients come, how many and how do their condition. For anticipating that conditions, the ER HCWs need good arrangement especially in the rapid identification of patients,  therefore patients can be classified based on the type and level of emergency. ER requires HCWs who have triage standard operational procedures (SOP) compliance to make sure the effective services. The factors associated with HCWs compliance are internal factors and external factors. The internal factors are  level of education, knowledge, motivation, age and working period. The external factors are  supervision, reward and punishment system. Key Word: Triage, level of education, knowledge, compliance of health care workers